THE INFLUENCE OF BRAND IMAGE ON COLLEGE CHOICE DECISIONS THROUGH BRAND TRUST - Muhammad Caesar Akbar; Syaifuddin Syaifuddin; Fajar Rezeki Ananda Lubis (Yayasan Nuraini Ibrahim Mandiri, 2026)
Competition among vocational higher education institutions in Indonesia, particularly Aviation Polytechnics, is intensifying, necessitating marketing strategies capable of building positive perceptions and trust among prospective students. This study aims to analyze the relationship between brand image, brand trust, and students' decisions to study at Aviation Polytechnics in Indonesia using a Systematic Literature Review (SLR) approach. The review process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and included a search for related articles. The synthesis results indicate that a positive brand image, reflected in the institution's reputation, educational service quality, and other factors, increases prospective students' brand trust. Furthermore, brand trust has been shown to strengthen prospective students' confidence in making decisions about choosing a university. Furthermore, the synthesis indicates that brand trust acts as a mechanism explaining how brand image influences university choice decisions, although some studies have found that the influence of brand image can also occur directly depending on the characteristics of the institution and the research context. This study provides a theoretical contribution by integrating the concepts of brand image, brand trust, and university choice decisions within a higher education marketing framework.